Small bowel ulcers: when is it not inflammatory bowel disease ?. Issue 3 (May 2019) - Keuchel, Martin; Kurniawan, Niehls; Baltes, Peter
Abstract : Purpose of review: Increasing use of small bowel endoscopy unravels ulcers in a relevant number of patients. Although often attributed to inflammatory bowel disease (IBD), these ulcers may be unspecific or caused by a variety of other diseases. This review summarizes the recent literature related to differential diagnosis of small bowel ulcers. Recent findings: NSAID enteropathy is the major differential diagnosis to IBD in patients with small bowel ulcers. Intestinal tuberculosis must be considered in patients at risk. Rare causes for small bowel ulcers are autoinflammatory, neoplastic, vascular diseases, or nontuberculous infections. Morphology of small bowel ulcers cannot provide a reliable differentiation, and even histology is not specific in all cases. History with special focus on NSAID medication and clinical symptoms not typical for IBD, laboratory tests in the search of systemic disease, and microbiologic testing of biopsies can be helpful. Genetic testing allows identification of few rare entities like defects in prostaglandin metabolism. Summary: Due to a massive overlap in the endoscopic appearance of small bowel ulcers between possible causes, diagnosis should be based on broad information also including history, histology, imaging, and laboratory tests.